2018
DOI: 10.2147/ott.s156814
|View full text |Cite
|
Sign up to set email alerts
|

NDRG3 facilitates colorectal cancer metastasis through activating Src phosphorylation

Abstract: BackgroundNDRG3 is an N-myc downregulated gene (NDRG). The aim of this article was to identify the role of NDRG3 in colorectal cancer (CRC) and to determine the mechanism underlying its function.MethodsUsing immunohistochemical staining, expression and clinicopathological variables of NDRG3 were analyzed in 170 CRC samples. Overexpression of NDRG3 was employed in SW1116 cells, downregulation of NDRG3 was achieved in RKO cells, then migration and invasion assays were performed in vitro, and a mouse model was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 32 publications
1
15
0
Order By: Relevance
“…Next, we attempted to identify the genes regulated by miR‐122‐5p and the luciferase assays verified that NDRG3 was one of its targets. NDRG3 is considered an oncogene in hepatocellular carcinoma and colorectal cancer 53,54 . By performing a series of experiments, we identified that NDRG3 was upregulated in OS tissues and cell lines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Next, we attempted to identify the genes regulated by miR‐122‐5p and the luciferase assays verified that NDRG3 was one of its targets. NDRG3 is considered an oncogene in hepatocellular carcinoma and colorectal cancer 53,54 . By performing a series of experiments, we identified that NDRG3 was upregulated in OS tissues and cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…NDRG3 is considered an oncogene in hepatocellular carcinoma and colorectal cancer. 53,54 By performing a series of experiments, we identified that…”
Section: Discussionmentioning
confidence: 99%
“…Then a pro-tumorigenic activity was reported for a member of the NDRG family, NDRG3, when it was known to be associated with prostate cancer [23]. Later, in the last five years of studies have elucidated additional roles of NDRG3 in various hypoxia responses, including cell proliferation, double-strand break repair, metastasis, and HIF regulation [24][25][26][27][28][29]. In this study, we determined the crystal structure of a truncated human NDRG3 fragment comprising residues from 29 to 320 (NDRG3 ΔNC), on the basis of its solubility and crystallizability.…”
Section: Discussionmentioning
confidence: 99%
“…In lieu of the lactate-mediated NDRG3 signaling, NDRG3 provokes anti-apoptotic processes during the hypoxia postcondition by regulating adenosine A2a receptors [26], activates Src phosphorylation in colorectal cancer progression [27], and promotes hepatocellular carcinoma metastasis via regulating turnover of β-catenin [28]. On the other hand, NDRG3 is involved in anti-metastatic functions, by dissociating the coactivator p300 from HIF-1a [29].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, NDRG family members are tumor-associated proteins and their dysregulation may result in tumorigenesis (5). NDRG3 has been reported to promote colorectal cancer metastasis by activating Src phosphorylation (6), and is associated with poor survival in non-small cell lung cancer (7). However, the role of NDRG3 and regulatory mechanisms of NDRG3 in gastric cancer remain unclear.…”
Section: Introductionmentioning
confidence: 99%